2020
DOI: 10.20944/preprints202003.0042.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virtual Screening of Inhibitors Against Spike Glycoprotein of 2019 Novel Corona Virus: A Drug Repurposing Approach

Abstract: The novel coronavirus (2019-nCoV) is a human and animal pathogen recently emerged in the city of Wuhan in Hubei province of China, causing a spectrum of severe respiratory illnesses. Corona viruses makes entry in to human cells through its spike (S) protein that binds to cell surface receptors. Wide spread of 2019-nCoV has been attributed to relatively high affinity of S protein to its receptor. Although S protein is a highly importantdrug target, unavailability of a high-resolution crystal structure and solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 8 publications
1
37
0
Order By: Relevance
“…Structural investigations indicated that ACE-2 from these systems can efficiently interact with RBD of SARS-CoV-2, inducing them all to serve as promising hosts for the virus infection (Mathewson et al, 2008;Poon & Peiris, 2020). Furthermore, it can be deduced that small molecular and ligands inhibitors that can limit the interaction of ACE-2 with RBD should be developed to combat the spreading CoV epidemic Senathilake et al, 2020). Isolating and cultivating CoV in vitro may not usually be practical or demand particular facilities that are not accessible in every bioresearch laboratory.…”
Section: Enzyme Inhibitors As Therapeutic Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural investigations indicated that ACE-2 from these systems can efficiently interact with RBD of SARS-CoV-2, inducing them all to serve as promising hosts for the virus infection (Mathewson et al, 2008;Poon & Peiris, 2020). Furthermore, it can be deduced that small molecular and ligands inhibitors that can limit the interaction of ACE-2 with RBD should be developed to combat the spreading CoV epidemic Senathilake et al, 2020). Isolating and cultivating CoV in vitro may not usually be practical or demand particular facilities that are not accessible in every bioresearch laboratory.…”
Section: Enzyme Inhibitors As Therapeutic Platformsmentioning
confidence: 99%
“…Scientist have pointed out that among several targets, the SP as fusogenic envelope glycoprotein of SARS CoV, is a promising site for treatment of infectious diseases (Li et al, 2018;Licitra et al, 2013). SPs mediate CoV fusion and the entry of the CoV genetic material into the human cell (Senathilake et al, 2020;Struck et al, 2012). Afterwards, a SP-selective strategy, when used at the initial phase of CoV infection is probably considered as a potential approach to mitigate infection inside the body.…”
Section: Introductionmentioning
confidence: 99%
“…Binding sites obtained from COACH-D was compared with identified binding sites of crystallized structure, PDB ID: 2GHV, which was already considered as a template for homology modeling for our query protein. Results generated from COACH server was further compared with previous studies on protein-protein docking, molecular dynamics and virtual screening studies on SARS-CoV-2 spike glycoprotein (nCoV-SP) as well human ACE-2 receptor [26][27][28][29][30][31][32]. The binding site residues, thus, selected from experimental studies as well as from bioinformatics tools thus provided a better platform for reliable docking studies.…”
Section: Binding Site Identificationmentioning
confidence: 99%
“…Drug re-purposing means that by examining existing drugs, they will find therapeutic effects on new diseases (Aggarwal et al, 2020;Khan, Jha, et al, 2020;Senathilake et al, 2020). BSAAs are small molecules that can inhibit different infections by blocking the viral replication (Pant et al, 2020;Xiong et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%